Between memories and spaces: public art in the construction of cultural landscapes - Dala Bernardina, Jovani (Revista do Colóquio, 2024)
We intend to present the cultural landscape existing in the municipalities of Santa Leopoldina, Santa Maria de Jetibá and Santa Teresa, in the Central-Mountainous region of Espírito Santo, based on local public art. In the text, we explore the dialogue between memory, public art and the transformation of the landscape. We conclude that public art can play a role in preserving cultural memory as well as generating belonging and re-significations, strengthening regional identity.